Affective and Emotional Economies in Medieval and Early Modern Europe
X, 278 p.
Keywords: This book analyzes how acts of feeling at a discursive, somatic, and rhetorical level were theorized and practiced in multiple medieval and early-modern sources (literary, medical, theological, and archival). It covers a large chronological and geographical span from eleventh-century France, to fifteenth-century Iberia and England, and ending with seventeenth-century Jesuit meditative literature. Essays in this book explore how particular emotional norms belonging to different socio-cultural communities (courtly, academic, urban elites) were subverted or re-shaped; engage with the study of emotions as sudden, but impactful, bursts of sensory experience and feelings; and analyze how emotions are filtered and negotiated through the prism of literary texts and the socio-political status of their authors.